Economic resilience: The case of Poland and certain European regions - Masik, Grzegorz (IGiPZ PAN, 2016)
The study of economic resilience represents a relatively new subject of debate within the framework of regional studies. Here, the author firsts presents the evolutionary approach to resilience, and within it the agency perspective; before refocusing on the macroeconomic policy pursued in Poland, which is deemed to have spared the country and many of its regions from the recession otherwise experienced so widely during the crisis in Europe. The author then turns to a characterisation of eight European regions, including one in Poland, describing the actions taken and strategies pursued with a view to counteracting the negative effects of the crisis, and building economic resilience to future events of the same kind.
24 cm
Keywords: economic resilience; evolutionary approach; agency perspective; economic crisis; Poland; European regions; Pomorskie region

Geographia Polonica Vol. 93 No. 4 (2020), Contents (IGiPZ PAN, 2020)
24 cm
Keywords: Geography

Thermal regime of the Vistula River mouth and the Gdańsk Bay - Graf, Renata. Autor; Vyshnevskyi, Viktor. Autor (IGiPZ PAN, 2023)
Surface water temperature characteristics of the Vistula River mouth and the Gdańsk Bay were determined on the basis of available observations, remote sensing and hydrodynamic models. The water temperature in the Vistula River and the Gdańsk Bay was found to be much higher than the air temperature. In recent decades, the water temperature in the Vistula River mouth and the Gdańsk Bay has increased significantly. It has been determined that water temperature in the bay is affected not only by air temperature, but also by water discharge of the Vistula River and wind.
24 cm
Keywords: water temperature; air temperature; remote sensing; coastal zone; Baltic Sea